2013
DOI: 10.19026/bjpt.4.5407
|View full text |Cite
|
Sign up to set email alerts
|

Lead Organ and Tissue Toxicity: Roles of Mitigating Agents (Part 1)

Abstract: Lead is one of the metals whose toxicological effect in humans and animals is of clinical concerned as reported by researchers. Quite a number of chemical agents have been reported to ameliorate lead associated toxicological effects especially in animal studies. This literary study reviewed reported toxicological effect of lead on the liver, kidney and brain with emphasis on the roles of mitigating chemical agents. In this review it was observed that his to patho logical changes in lead associated he patotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 51 publications
3
16
0
Order By: Relevance
“…Several reports have indicated that lead can cause neurological, hematological, gastrointestinal, reproductive, circulatory and immunological pathologies, all of them related to the dose and the duration of time of lead exposure [9 &10]. Toxicities due to lead exposure have been attributed to the ability of lead to induce oxidative stress through the generation of reactive oxygen species [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have indicated that lead can cause neurological, hematological, gastrointestinal, reproductive, circulatory and immunological pathologies, all of them related to the dose and the duration of time of lead exposure [9 &10]. Toxicities due to lead exposure have been attributed to the ability of lead to induce oxidative stress through the generation of reactive oxygen species [11].…”
Section: Introductionmentioning
confidence: 99%
“…Plant extracts and materials of animal origin were also observed to protect against lead induced toxicity in experimental animals. The abilities of these extracts to mitigate these toxicities were attributed to the antioxidant properties of principles contained in these extracts [11].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure of human body to toxic substances may affect multiple organ systems and cause morphological, biochemical and physiological changes, including impaired kidney function and haematological disorders [36][37][38]. Hematopoietic system is the main target of some drug which adversely affects heme synthesis enzymes, the normal production rate of erythropoietin, normal range, morphology and distribution of various blood cells [39,40]. Toxic drugs damage erythrocyte and affect its oxygen-carrying capacity thereby increase the risk of developing hypertension and cardiac arrest [41].…”
Section: Discussionmentioning
confidence: 99%
“…Al-Naggar et al (2003) reported that N. sativa can prevent the damage of spatial memory after scopolamine administration and reduced the acetylcholinesterase (AChE) activity as well as oxidative stress of the brain tissue in rats (Hosseini et al, 2015). Researches using animal models have shown that lead toxicity could be associated with oxidative stress via the generation of reactive oxygen species and can be mitigated by some antioxidants, materials of animal origin and extracts of plant origin (Adikwu et al, 2013). The present findings agree to the fact that natural compounds that are rich in antioxidants help to reduce oxidative stress thus alleviating the effect of oxidative agents (Ahamed and Siddiqui, 2007).…”
Section: Discussionmentioning
confidence: 99%